2020
DOI: 10.1002/mbo3.1095
|View full text |Cite
|
Sign up to set email alerts
|

Captivity affects diversity, abundance, and functional pathways of gut microbiota in the northern grass lizard Takydromus septentrionalis

Abstract: Animals in captivity undergo a range of environmental changes from wild animals. An increasing number of studies show that captivity significantly affects the abundance and community structure of gut microbiota. The northern grass lizard (Takydromus septentrionalis) is an extensively studied lacertid lizard and has a distributional range covering the central and southeastern parts of China. Nonetheless, little is known about the gut microbiota of this species, which may play a certain role in nutrient and ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 89 publications
4
51
0
Order By: Relevance
“…In reptiles, that the gene functions of the gut microbes are associated with metabolism has been reported for the timber rattlesnake Crotalus horridus (McLaughlin et al, 2015), the crocodile lizard Shinisaurus crocodilurus (Tang et al, 2020), and the northern grass lizard Takydromus septentrionalis (Zhou et al, 2020). Similar results have also been reported for birds (Wang et al, 2018) and mammals (Zhao et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In reptiles, that the gene functions of the gut microbes are associated with metabolism has been reported for the timber rattlesnake Crotalus horridus (McLaughlin et al, 2015), the crocodile lizard Shinisaurus crocodilurus (Tang et al, 2020), and the northern grass lizard Takydromus septentrionalis (Zhou et al, 2020). Similar results have also been reported for birds (Wang et al, 2018) and mammals (Zhao et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…Seasonal variation in diets may lead to changes in the gut microbiota (Kartzinel et al, 2019), and exposure of host animals to artificial environments (e.g., animals in captivity) may lead to an increase in the abundance of human disease-related functional genes in the gut microbes (Tang et al, 2020;Zhou et al, 2020). Taken together, the gut microbial community is affected by the host's genetic background, diets and individual status and, in turn, affects the physiological, behavioral and even evolutionary processes of the host.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that in both species the most functionally distinct categories were focused on metabolism, genetic information processing and environmental information processing at the first function level, followed by gene functions associated with membrane transport, replication and repair, amino acid metabolism and carbohydrate metabolism at the second level, and transporters and ABC transporters at the third level. In reptiles, that the gene functions of the gut microbes are associated with metabolism has been reported for the timber rattlesnake Crotalus horridus ( Mclaughlin, Cochran & Dowd, 2015 ), the crocodile lizard Shinisaurus crocodilurus ( Tang et al, 2020 ), and the northern grass lizard Takydromus septentrionalis ( Zhou et al, 2020 ). Similar results have also been reported for birds ( Wang et al, 2018 ) and mammals ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, early growth, household location, and antibiotic experiences during pregnancy are correlated with the early gut microbial composition in humans ( Vatanen et al, 2019 ). Seasonal variation in diets may lead to changes in the gut microbiota ( Kartzinel et al, 2019 ), and exposure of host animals to artificial environments (e.g., animals in captivity) may lead to an increase in the abundance of human disease-related functional genes in the gut microbes ( Tang et al, 2020 ; Zhou et al, 2020 ). Taken together, the gut microbial community is affected by the host’s genetic background, diets and individual status and, in turn, affects the physiological, behavioral and even evolutionary processes of the host.…”
Section: Introductionmentioning
confidence: 99%
“…The lizrads’ gut microbial community compositions and structures were similar to those observed in mammals, and previous studies have documented general patterns. Further, gut bacterial diversity did not depend on the diversification of lizard hosts [ 33 ], but it varied along altitudes, diet and captive environment [ 2 , 14 , 34 , 35 , 36 , 37 , 38 ], and changed due to climate warming [ 32 ]. There was no significant difference in gut bacterial diversity between juveniles and adults [ 35 ], but males had significantly higher gut bacterial diversity and richness than do females [ 39 ], while non-gestation females had higher gut bacterial richness than do late-gravid females [ 11 ].…”
Section: Introductionmentioning
confidence: 99%